Dari Gotong Royong ke Komodifikasi: Pergeseran Bentuk Ekonomi Melekat di Komunitas Pesisir Terdampak Banjir Rob di Kecamatan Sayung, Demak - Purwanti, Tari; Azhar, Fadhilatul (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
Tidal flooding along the coast of Sayung, Demak, has transformed the community's socio-economic structure, particularly in the practice of mutual cooperation (gotong royong), which has now become a form of paid labor. This study aims to explain the commodification of mutual cooperation and how the community negotiates changing values of solidarity amidst ecological pressures. Using a qualitative approach with economic ethnography methods, the study involved 28 informants from various backgrounds, including fishermen, fishpond laborers, construction workers, and women who manage food stalls. The results indicate that the shift from voluntary mutual cooperation to a paid system is not simply a sign of weakening social morality, but rather a form of adaptation to economic needs and the loss of livelihoods. Using Karl Polanyi's framework of the embedded economy, this phenomenon is understood as a process of disembedding and re-embedding, in which market logic is adjusted to remain aligned with local social norms and moral values. These findings confirm that the Sayung community has formed a hybrid economy that maintains social solidarity amidst market pressures and ecological crises.